KOMPETENSI MANAJERIAL KEPALA SEKOLAH PADA SMP TERPENCIL NEGERI 3 BANDAR BARU PIDIE JAYA - Fitriliana .; Cut Zahri Harun; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The purpose of this study is to describe and analyze: (1) Competence managerial principals in a remote SMP Negeri 3 Bandar Baru Pidie Jaya in planning school activities; (2) the principal managerial competence in implementing the plan school activities on a remote SMP Negeri 3 Bandar Baru Pidie Jaya; and (3) the principal obstacle encountered in implementing managerial competence in a remote SMP Negeri 3 Bandar Baru Pidie Jaya. This research uses descriptive method with qualitative approach. Data collection techniques used were observation, interviews, and documentation. The subjects are: principals, teachers and school committees. The results showed that: (1) Competence managerial principals in planning school activities has been good, it is seen from there RKS, the committee PSB, the organizational structure of the school, the structure of the school committee, school financial management, personnel management, management of student, curriculum management and public relations, but in the management of facilities and infrastructure, information management systems have not been managed optimally; (2) the principal managerial competence in implementing the action plan the school has not reached the maximum results, as seen in the educators in excess, lack of innovation in teaching methods, laboratory and library management is not optimal; (3) the principal obstacle encountered in implementing the managerial competence of teachers is the lack of discipline, lack of facilities and infrastructure, there is no motivation from parents to students.Keywords: managerial competence,  principals, and school isolated